Health care importance of Treponema pallidum, Chagas disease and Human immunodeficiency virus 1 among Amerindians of Argentina: an observational study = Importancia en el sistema de salud de la infección por Treponema pallidum, la enfermedad de Chagas y el virus de la inmunodeficiencia humana 1 en amerindios de Argentina: un estudio observacional - Eirin, Maria Emilia; Delfino, Cecilia María; Pedrozo, Williams René; Malan, Richard; Puca, Alberto; de Rissio, Ana María; Espejo, Rogelio; Gallo Vaulet, Maria Lucia; Rodríguez Fermepin, Marcelo; Biglione, Mirna Marcela; Berini, Carolina Andrea (Asociación Argentina de Microbiología, 2018)
The objective of this study was to estimate the prevalence of Treponema pallidum, Trypanosoma cruzi and Human immunodeficiency virus 1 (HIV-1) in five Amerindian populations of Argentina. A retrospective study was conducted among 857 Amerindian populations (112 Kollas, 298 Mbyá-guaraníes, 79 Sagua Huarpes, 368 Wichis) from 2007 to 2010. Screening and confirmation of T. pallidum, T. cruzi and HIV-1 were performed. T. pallidum and T. cruzi infections were detected in all communities with an overall prevalence rate of 4.2% and 16.8%, respectively. Although HIV was not detected, syphilis and Chagas disease represent a challenge for the health care system and the reinforcement of public health strategies is necessary considering the socioeconomic isolation of these populations.